Basic assessment on adding platelet measurement to legal health checkup in Japan: A cross-sectional and 20-year longitudinal study - Kasuya, Kayoko; Fukai, Kota; Watanabe, Yuuya; Furuya, Yuko; Nakazawa, Shoko; Honda, Toru; Hayashi, Takeshi; Nakagawa, Toru; Tatemichi, Masayuki; Korenaga, Masaaki (Frontiers in Public Health, 2023)
Background: In Japan, health checkups for workers are legally compulsory. Considering legal health checkup items is important for Japanese workers' health problems. Until today, the legal health checkup items for blood cell counts include only red blood cell counts and haemoglobin, but not platelet counts. This study aimed to investigate the significance of measuring platelets in workers by showing the association between FIB-4 index (FIB-4), which can be easily calculated from factors including platelet counts, and viral hepatitis infection. Method: Both cross-sectional and longitudinal analyses were conducted on the comprehensive medical examinations of male workers. In fiscal year (FY) 2019, a logistic regression model was applied to 12,918 examinees. For 13,459 examinees (mean age=47.5 ± 9.3 SD) in FY2000 was set to be followed until FY2019. A total of 149,956 records between FY2000 and FY2019 were analyzed cross-sectional, and 8038 men who were consecutively examined to FY2019 at the longest were analyzed longitudinal. Receiver Operating Characteristic (ROC) curve-Area under the ROC curve (ROC-AUC) and Cox proportional methods were used to examine the association between platelet-related indices and viral hepatitis infection. Results: Logistic regression showed that the risk of FIB-4 ≥ 2.67 was mostly associated with hepatitis C virus anti-body (HCV Ab) positivity (odds ratio (OR) =2.51, 95% confidence interval (CI)=1.08-5.86), while negatively associated with body mass index (BMI) (OR=0.54, 95%CI=0.30-0.97), and not associated with the presence of fatty liver. To detect HVC Ab positivity, ROC-AUC showed more effectiveness in FIB-4 than in AST/ALT ratio (0.776, 95%CI=0.747- 0.773 vs 0.552; 95%CI=0.543-0.561). The Cox analysis showed that the risk of FIB-4 ≥2.67 was closely associated with hepatitis B virus surface antigen (HBsAg) (hazard ratio (HR)=3.1, 95%CI=2.0-4.6) and HCV Ab positivity (HR=3.2, 95%CI=2.0-5.0). Conclusions: Our results suggest that it might be worth considering that usage of information on platelets in legal health checkups could be some help not to overlook workers with hepatitis virus carriers as a complementary countermeasure, although further investigations are needed into its practical application.